A high-stability hydroprocessing catalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202310222296.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-09
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-03-09
AI Technical Summary
[0008]上述现有技术对于解决加氢催化剂使用时的抗积碳性能和长周期运行的稳定性还需要提高
[0024] Compared with the prior art, the present invention provides a high-stability hydrogenation catalyst, its preparation method, and its application, which have the following advantages: Through in-depth research, the inventors discovered that by introducing excess Na ions during the preparation of alumina dry gel, and by controlling the number of washing cycles and the amount of washing water, the hydrogenation catalyst contains appropriate amounts of sodium and sulfur elements. The sodium and sulfate elements work together to make the hydrogenation catalyst suitable for long-term stable operation of hydrogenation devices, exhibiting high activity and stability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to a highly stable hydrogenation catalyst, its preparation method, and its application; more specifically, it relates to a highly stable hydrogenation catalyst particularly suitable for long-term operation of hydrogenation units, its preparation method, and its application. Background Technology
[0002] Most supported catalysts are prepared using impregnation methods, such as various hydrogenation catalysts. Alumina is commonly used as a support material for these catalysts. Carbon deposition is the main cause of deactivation in hydrogenation catalysts, and reducing the rate and amount of carbon deposition is a key focus in catalyst development.
[0003] To improve the activity and stability of hydrotreating catalysts, it is often necessary to chemically modify the alumina support, such as by adding additives such as silicon, phosphorus, fluorine, boron, zirconium, titanium, magnesium, gallium, vanadium, manganese, copper, and zinc. These modifications serve to alter the acidity of the alumina, change the interaction between the active components and the alumina, and improve the thermal stability of the alumina.
[0004] CN00110018.1 discloses a hydrogenation catalyst and its preparation method. The catalyst uses Group VIB and Group VIII metals as hydrogenation active components, fluorine as an auxiliary agent, and supports one or a mixture of boron, silicon, phosphorus, magnesium, titanium, zirconium, and gallium as auxiliary agents. The key technology is the use of co-precipitation method for preparation. Some active metals may enter the bulk phase or be covered by alumina particles during co-precipitation and extrusion, which will reduce the utilization rate of active metals.
[0005] CN200410050777.5 discloses a macroporous alumina carrier and its preparation method. It contains boron oxide and may also contain additives such as phosphorus, silicon, zirconium, and titanium. In the preparation process of the alumina carrier of this invention, boric acid is dissolved in water or a colloidal acid at above room temperature, and then added to a mixture of alumina precursor and a physical pore-expanding agent. The mixture is then kneaded, shaped, dried, and calcined to obtain the final carrier.
[0006] CN201510196358.0 discloses a method for preparing a hydrogenation demetallization catalyst, comprising the following: (1) impregnating physical pore expander I with alkali metal element solution I and hydrogenation active component impregnation liquid I respectively, and impregnating physical pore expander II with alkali metal element solution II and hydrogenation active component impregnation liquid II. After drying, physical pore expanders I and II are sprayed with ammonium salt solution for later use; (2) mixing physical pore expanders I and II obtained in step (1) with boehmite dry adhesive powder, chemical pore expander, extrusion aid, and adhesive solvent to form a plastic body, extruding strips and molding materials are heat-treated, and the treated materials are dried and calcined to obtain a modified alumina support; (3) impregnating the modified alumina support with hydrogenation active component impregnation liquid III, and then drying and calcining to obtain the catalyst.
[0007] CN200710118009.2 discloses a heavy oil hydrotreating catalyst and its preparation method. The catalyst contains a support and an effective amount of at least one metal component selected from Group VIII and at least one metal component selected from Group VIB. The support is a boron-containing composite alumina support. Based on the total amount of the support, the boron content in the support is 0.3-5% by weight. The acidity of the support is 0.2-0.5 mmol / g. The amount of weak acid below 250℃ accounts for 50-100% of the total acidity, while the amount of strong acid above 450℃ accounts for 0-5% of the total acidity.
[0008] The existing technologies mentioned above still need to be improved to address the issues of carbon buildup resistance and long-term operational stability of hydrogenation catalysts. Summary of the Invention
[0009] To address the problems existing in the prior art, the present invention provides a highly stable hydrogenation treatment catalyst, its preparation method, and its application. The hydrogenation treatment catalyst is suitable for long-term stable operation of hydrogenation devices and has high activity and stability.
[0010] This invention discloses a highly stable hydrogenation catalyst, which, based on the weight of the final hydrogenation catalyst, contains 8% to 50% active metal (calculated as oxide), 40% to 90% alumina, 0.08% to 1.8% alkali metal oxide (calculated as oxide), and less than 5.0% sulfate; preferably, it contains 15% to 36% active metal (calculated as oxide), 55% to 85% alumina, 0.15% to 1.2% alkali metal oxide (calculated as oxide), and less than 3.0% sulfate, and more preferably, the sulfate content is 0.5% to 2.5%; the alkali metal is at least one selected from lithium, sodium, potassium, rubidium, cesium, and francium, preferably sodium and / or potassium, and more preferably sodium.
[0011] In the hydrotreating catalyst of the present invention, the active metal is a Group VIB metal and / or a Group VIII metal, wherein the Group VIB metal is Mo and / or W, and the Group VIII metal is Ni and / or Co. Based on the weight of the final hydrotreating catalyst, it contains 6 wt% to 38 wt% of Group VIB metal oxides, preferably 13% to 30%, and 2 wt% to 12 wt% of Group VIII metal oxides, preferably 2% to 6%.
[0012] The hydrogenation catalyst of the present invention may contain an auxiliary agent, which is selected from one or more of silicon, phosphorus, fluorine, boron, etc. Based on the weight of the final hydrogenation catalyst, the content of the auxiliary agent, calculated by element, is 0.3% to 10%, preferably 0.5% to 5%.
[0013] In the hydrogenation catalyst of the present invention, the mass ratio of alkali metal oxide to sulfate (calculated as oxide) is 0.08 to 1.8, preferably 0.10 to 0.60.
[0014] A method for preparing a highly stable hydrogenation catalyst includes the following steps: (1) An acidic aluminum sulfate solution and an alkaline soluble sodium salt solution (preferably sodium aluminate solution) are subjected to a co-precipitation reaction. After the reaction, the mixture is filtered, washed, and dried to obtain alumina dry gel. An alkali metal salt (preferably sodium carbonate) or a solution containing an alkali metal salt is added to the reaction system before, during, or after the co-precipitation reaction. The mixture is washed until the mass content of the alkali metal in the alumina dry gel powder, calculated as oxides, in the final alumina powder is 0.1% to 2.5%, preferably 0.5% to 1.5%, and the mass content of sulfate in the final alumina powder is 0.3% to 6.0%, preferably 0.8% to 4.0%. (2) The alumina dry adhesive in step (1) is subjected to molding treatment. During or after molding, an active metal is introduced, and the final hydrogenation catalyst is obtained after drying or drying and calcination.
[0015] In the method of this invention, the co-precipitation reaction between the acidic aluminum sulfate solution and the alkaline soluble sodium salt solution (preferably sodium aluminate solution) in step (1) specifically includes the following process: 1) Under stirring conditions, aluminum sulfate solution and sodium aluminate solution undergo a gelation reaction at suitable pH and temperature to prepare alumina dry gel precursor; 2) Add a sodium carbonate solution to control the pH of the material to 5.5~10.5, preferably 7.5~9.5, and then carry out the aging operation; 3) After aging, filter, wash and dry to obtain alumina dry gel.
[0016] Further, in step 1), the concentration of the aluminum sulfate compound solution, calculated as Al2O3, is 0.5g~10g / 100mL, preferably 2g~6g / 100mL. The concentration of the sodium aluminate compound solution, calculated as Al2O3, is 5g~30g / 100mL, preferably 10g~25g / 100mL. The gelation temperature is 30℃~95℃, preferably 50℃~80℃; the gelation pH value is 4.5~10.0, preferably 5.5~9.0. The alumina dry gel precursor can also undergo an aging process before step 2, with an aging time of 10min~100min.
[0017] Furthermore, in step 2), the pH of the system increases by 0.2 to 5.0 after adding a sodium carbonate solution, preferably by 0.5 to 3.0; the aging temperature is 30℃ to 95℃, preferably 50℃ to 90℃; and the aging time is controlled to be 0.5h to 8h, preferably 1.5h to 4.5h.
[0018] Furthermore, in step 3), the filtration method can be plate and frame filtration, belt filtration, etc. The washing time or number of times is controlled according to the sodium and sulfur content in the dry adhesive. For example, distilled water can be used for washing 1-3 times. The filter cake can be statically dried or dynamically dried. The drying temperature is 60℃~200℃ and the drying time is 0.5h~12.0h. The preferred drying temperature is 80℃~160℃ and the drying time is 1.0h~8.0h. The dry basis of the alumina dry adhesive powder should be 60wt%~80wt%.
[0019] Furthermore, the aluminum hydroxide dry adhesive in step 3), after high-temperature calcination (calcination at 500℃ for 3 hours), has the following properties: specific surface area of 200-500 μm. 2 / g, pore volume is 0.5~1.3mL / g, and average pore size is 5nm~16nm.
[0020] In the method of this invention, the alumina dry adhesive in step (2) is shaped using conventional methods, such as mixing the alumina dry adhesive, extrusion aid, and adhesive solvent evenly, and then kneading or rolling to obtain the shaped alumina carrier. The alumina carrier can be made into strips, spheres, etc., as needed. Suitable adhesive solvents are various organic acids, inorganic acids, and those that can ionize H+. + The compounds used include nitric acid, oxalic acid, acetic acid, propionic acid, etc., and the adhesive solvent used is one or more of the above-mentioned substances. The extrusion aid is known in the art and may include various alcohols, cellulose, guar gum, etc.
[0021] In the method of this invention, the active metal in step (2) is introduced after the alumina dry adhesive is formed. The introduction is carried out by impregnation, which can be either equal volume impregnation or non-equal volume impregnation. Other additives may be introduced before or simultaneously with the introduction of the active metal. The additives are selected from one or more of silicon, phosphorus, fluorine, boron, etc.
[0022] In the method of the present invention, the drying and calcination in step (2) adopt existing technical conditions, such as a drying temperature of 50℃~200℃, preferably 110℃~160℃, and a drying time of 0.5h~20h, preferably 1h~6h; a calcination temperature preferably of 350℃~900℃, more preferably 350℃~600℃, and a calcination time of 0.5h~20h, preferably 1h~6h.
[0023] A hydrotreating method, wherein the method employs the above-mentioned hydrotreating catalyst, and the operating conditions are as follows: using VGO with a dry point of not less than 500°C as feedstock, a total reaction pressure of 6.0 MPa ~ 20.0 MPa, and a volume hourly space velocity of 0.3 h⁻¹. -1 ~3.0 h -1The hydrogen-to-oil ratio is 400:1 to 1800:1, and the reaction temperature is 300℃ to 420℃.
[0024] Compared with the prior art, the present invention provides a high-stability hydrogenation catalyst, its preparation method, and its application, which have the following advantages: Through in-depth research, the inventors discovered that by introducing excess Na ions during the preparation of alumina dry gel, and by controlling the number of washing cycles and the amount of washing water, the hydrogenation catalyst contains appropriate amounts of sodium and sulfur elements. The sodium and sulfate elements work together to make the hydrogenation catalyst suitable for long-term stable operation of hydrogenation devices, exhibiting high activity and stability. Implementation
[0025] The technical features of the present invention are further described below through embodiments, but it should not be considered that the present invention is limited to these embodiments. The percentages mentioned are weight percentages.
[0026] Example 1 Add 1L of deionized water to the container and heat it to 60℃. At the same time, add an aluminum sulfate solution containing 9g / 100mL of Al2O3 and a sodium aluminate solution containing 8g / 100mL of Al2O3. Control the pH value to 9.5 and add the materials over a period of 60 minutes.
[0027] After stopping the feeding, the system was aged for 20 minutes under the above temperature and pH conditions. Then, a Na2CO3 solution was added, with a Na2CO3 concentration of 6g Na2O / 100mL. The temperature was controlled at 95℃ and the pH was controlled at 9.8. The system was aged for another 2 hours and then filtered.
[0028] After washing three times, the filter cake was dried at 100℃ for 8 hours and then pulverized until more than 95% of the particles were smaller than 180 mesh to obtain dry adhesive powder A1.
[0029] Example 2 Add 1L of deionized water to the container and heat it to 40℃. At the same time, add an aluminum sulfate solution containing 1g / 100mL of Al2O3 and a sodium aluminate solution containing 28g / 100mL of Al2O3. Control the pH value to 5.0 and add the materials over a period of 60 minutes.
[0030] After stopping the feeding, the system was aged for 20 minutes under the above temperature and pH conditions. Then, a Na2CO3 solution was added, with a Na2CO3 concentration of 12g Na2O / 100mL. The temperature was controlled at 40℃ and the pH was controlled at 9.8. The system was aged for another 2 hours and then filtered.
[0031] After washing once, the filter cake is dried at 110℃ for 8 hours and then pulverized until more than 95% of the particles are smaller than 180 mesh to obtain dry adhesive powder A2.
[0032] Example 3 Add 1L of deionized water to the container and heat it to 40℃. At the same time, add an aluminum sulfate solution containing 3g / 100mL of Al2O3 and a sodium aluminate solution containing 18g / 100mL of Al2O3. Control the pH value to 8.0 and add the materials over a period of 60 minutes.
[0033] After stopping the feeding, the system was aged for 20 minutes under the above temperature and pH conditions. Then, a Na2CO3 solution was added, with a Na2CO3 concentration of 10g Na2O / 100mL. The temperature was controlled at 60℃ and the pH was controlled at 8.3. The system was aged for another hour and then filtered.
[0034] After washing once, the filter cake is dried at 120℃ for 7 hours and then pulverized until more than 95% of the particles are smaller than 180 mesh to obtain dry adhesive powder A3.
[0035] Example 4 Add 1L of deionized water to the container and heat it to 70℃. At the same time, add an aluminum sulfate solution containing 4g / 100mL of Al2O3 and a sodium aluminate solution containing 15g / 100mL of Al2O3. Control the pH value to 6.0 and add the materials over a period of 60 minutes.
[0036] After stopping the feeding, the system was aged for 20 minutes under the above temperature and pH conditions. Then, a Na2CO3 solution was added, with a Na2CO3 concentration of 10g Na2O / 100mL. The temperature was controlled at 80℃ and the pH was controlled at 9.5. The system was aged for another 3 hours and then filtered.
[0037] After washing three times, the filter cake was dried at 120℃ for 7 hours and then pulverized until more than 95% of the particles were smaller than 180 mesh to obtain dry adhesive powder A4.
[0038] Example 5 Add 1L of deionized water to the container and heat it to 70℃. At the same time, add an aluminum sulfate solution containing 5g / 100mL of Al2O3 and a sodium aluminate solution containing 19g / 100mL of Al2O3. Control the pH value to 8.0 and add the materials over a period of 60 minutes.
[0039] After stopping the feeding, the system was aged for 20 minutes under the above temperature and pH conditions. Then, a Na2CO3 solution was added, with a Na2CO3 solution concentration of 10g Na2O / 100mL. The temperature was controlled at 70℃ and the pH was controlled at 9.0. The system was aged for another 4 hours and then filtered.
[0040] After washing once, the filter cake is dried at 110℃ for 7 hours and then pulverized until more than 95% of the particles are smaller than 180 mesh to obtain dry adhesive powder A5.
[0041] Example 6 Add 1L of deionized water to the container and heat it to 60℃. At the same time, add an aluminum sulfate solution containing 3g / 100mL of Al2O3 and a sodium aluminate solution containing 13g / 100mL of Al2O3. Control the pH value to 8.0 and add the materials over a period of 60 minutes.
[0042] After stopping the feeding, the system was aged for 20 minutes under the above temperature and pH conditions. Then, a Na2CO3 solution was added, with a Na2CO3 solution concentration of 8g Na2O / 100mL. The temperature was controlled at 80℃ and the pH was controlled at 9.0. The system was aged for another 2 hours and then filtered.
[0043] After washing twice, the filter cake was dried at 160℃ for 2 hours and then pulverized until more than 95% of the particles were smaller than 180 mesh to obtain dry adhesive powder A6.
[0044] Example 7 Add 1L of deionized water to the container and heat it to 80℃. At the same time, add an aluminum sulfate solution containing 4g / 100mL of Al2O3 and a sodium aluminate solution containing 18g / 100mL of Al2O3. Control the pH value to 6.0 and add the materials over a period of 80 minutes.
[0045] After stopping the feeding, the system was aged for 60 minutes under the above temperature and pH conditions. Then, a Na2CO3 solution was added, with a Na2CO3 solution concentration of 12g Na2O / 100mL. The temperature was controlled at 90℃ and the pH was controlled at 8.5. The system was aged for another 3 hours and then filtered.
[0046] After washing once, the filter cake is dried at 180℃ for 2 hours and then pulverized until more than 95% of the particles are smaller than 180 mesh to obtain dry adhesive powder A7.
[0047] Comparative Example 1 Add 1L of deionized water to the container and heat it to 60℃. At the same time, add an aluminum sulfate solution containing 4g / 100mL of Al2O3 and a sodium aluminate solution containing 18g / 100mL of Al2O3. Control the pH value to 8.0 and add the materials over a period of 60 minutes.
[0048] After stopping the feeding, the system was aged for 20 minutes under the above temperature and pH conditions. Then, a Na2CO3 solution was added, with a Na2CO3 solution concentration of 10g Na2O / 100mL. The temperature was controlled at 60℃ and the pH was controlled at 9.5. The system was aged for another 4 hours and then filtered.
[0049] After washing four times, the filter cake was dried at 120℃ for 6 hours and then pulverized until more than 95% of the particles were smaller than 180 mesh to obtain dry adhesive powder A8.
[0050] Example 8 Take 300g of dry adhesive powder A1, add 6g each of citric acid and guar gum powder, mix well, and then slowly and evenly add 240g of nitric acid aqueous solution (containing 6.0g of nitric acid) over 10 minutes. Knead for 30 minutes, then extrude using a 1.7mm diameter clover-shaped perforated plate. Dry at 120℃ for 4 hours, then calcine at 500℃ for 3 hours. The calcined carrier is designated Z1. Carriers Z2, Z3, Z4, Z5, Z6, Z7, and Z8 are prepared using the same method with dry adhesive powders A2, A3, A4, A5, A6, A7, and A8, respectively.
[0051] Example 9 The calcined support strips Z1, Z2, Z3, Z4, Z5, Z6 and Z7 were used as the support for the example. They were impregnated with equal volumes of Mo, Ni and P solutions for 2 hours, dried at 120°C for 6 hours and calcined at 500°C for 2 hours to obtain catalysts, which were denoted as C1, C2, C3, C4, C5, C6 and C7, respectively. The catalyst composition is shown in Table 1.
[0052] Comparative Example 2 The calcined support strip Z8 was used as a comparative support. It was impregnated with an equal volume of Mo, Ni and P solution for 2 hours, dried at 120℃ for 6 hours, and calcined at 500℃ for 2 hours to obtain the catalyst, which was denoted as DC8. The catalyst composition is shown in Table 1.
[0053] Table 1 Properties of the prepared catalysts
[0054] *The content of sulfate and sodium oxide in the catalyst of this invention are measured values.
[0055] Example 10 This example is an experiment to evaluate the activity of the catalyst.
[0056] Catalyst activity evaluation experiments were conducted on a 100 ml small-scale hydrogenation apparatus. The catalyst was pre-sulfurized prior to the evaluation. The evaluation conditions were a total reaction pressure of 16.0 MPa and a volume hourly space velocity (VHSV) of 1.2 h⁻¹. -1 The hydrogen-to-oil ratio was 900:1, and the reaction temperature was 385℃. The properties of the feedstock oil used in the activity evaluation experiment are shown in Table 2, and the activity evaluation results are shown in Table 3. As can be seen from the data in the tables, the hydrogenation catalyst prepared using this invention exhibits significantly improved hydrogenation denitrification activity and stability, and a marked reduction in carbon deposit content, which can extend the operating cycle.
[0057] Table 2 Properties of Crude Oil
[0058] Table 3. Catalyst Activity Evaluation Results
Claims
1. A highly stable hydrogenation catalyst, characterized in that: Based on the weight of the final hydrotreating catalyst, it contains 8%–50% active metal (calculated as oxide), 40%–90% alumina, 0.08%–1.8% alkali metal oxide (calculated as oxide), and 0.5%–3.0% sulfate; the alkali metal is sodium; the mass ratio of alkali metal oxide to sulfate in the hydrotreating catalyst is 0.08–1.8; the hydrotreating catalyst is a vacuum wax oil hydrotreating catalyst. The active metal is a Group VIB metal and / or a Group VIII metal, wherein the Group VIB metal is Mo and / or W, and the Group VIII metal is Ni and / or Co, and based on the weight of the final hydrogenation catalyst, it contains 6 wt% to 38 wt% of Group VIB metal oxides and 2 wt% to 12 wt% of Group VIII metal oxides. The hydrogenation catalyst contains an auxiliary agent selected from one or more of silicon, phosphorus, fluorine, and boron. Based on the weight of the final hydrogenation catalyst, the auxiliary agent content, calculated as an element, is 0.3% to 10%.
2. The hydrogenation catalyst according to claim 1, characterized in that: Based on the weight of the final hydrotreating catalyst, it contains 15% to 36% active metals as oxides, 55% to 85% alumina, 0.15% to 1.2% alkali metal oxides as oxides, and 0.5% to 2.5% sulfate.
3. The hydrotreating catalyst according to claim 1, characterized in that: Based on the weight of the final hydrogenation catalyst, it contains 13% to 30% of Group VIB metal oxides and 2% to 6% of Group VIII metal oxides.
4. The hydrotreating catalyst according to claim 1, characterized in that: Based on the weight of the final hydrogenation catalyst, the content of the additives, calculated by element, is 0.5% to 5%.
5. The hydrotreating catalyst according to claim 1, characterized in that: The mass ratio of alkali metal oxides to sulfate in the hydrotreating catalyst is 0.10 to 0.60 (calculated as oxides).
6. A method for preparing the hydrotreating catalyst according to any one of claims 1-5, characterized in that: Includes the following steps: (1) Acidic aluminum sulfate solution and alkaline soluble sodium salt solution are subjected to a co-precipitation reaction. After the reaction, the mixture is filtered, washed, and dried to obtain alumina dry gel. An alkali metal salt or a solution containing an alkali metal salt is added to the reaction system before, during, or after the co-precipitation reaction. The mixture is washed until the mass content of alkali metal in the alumina dry gel powder, calculated as oxides, in the final alumina powder is 0.1% to 2.5%, and the mass content of sulfate in the final alumina powder is 0.3% to 6.0%. (2) The alumina dry adhesive in step (1) is subjected to molding treatment. During or after molding, an active metal is introduced, and the final hydrogenation catalyst is obtained after drying or drying and calcination.
7. The method according to claim 6, characterized in that: The soluble sodium salt solution in step (1) is a sodium aluminate solution; the alkali metal salt is sodium carbonate.
8. The method according to claim 6, characterized in that: In step (1), the alkali metals contained in the alumina dry adhesive powder are washed until the mass content of the alkali metals in the final alumina powder is 0.5%~1.5% as oxides and the mass content of sulfate in the final alumina powder is 0.8%~4.0%.
9. The method according to claim 7, characterized in that: The co-precipitation reaction between the acidic aluminum sulfate solution and the sodium aluminate solution in step (1) specifically includes the following process: 1) Under stirring conditions, aluminum sulfate solution and sodium aluminate solution undergo a gelation reaction at suitable pH and temperature to prepare alumina dry gel precursor; 2) Add a sodium carbonate solution to control the pH of the material to 5.5~10.5, and then carry out the aging operation; 3) After aging, filter, wash and dry to obtain alumina dry gel.
10. The method according to claim 9, characterized in that: In step 1), the concentration of the aluminum sulfate compound solution (calculated as Al2O3) is 0.5g~10g / 100mL, the concentration of the sodium aluminate compound solution (calculated as Al2O3) is 5g~30g / 100mL, the gelation temperature is 30℃~95℃, and the gelation pH value is 4.5~10.
0.
11. The method according to claim 10, characterized in that: In step 1), the concentration of the aluminum sulfate compound solution, calculated as Al2O3, is 2g~6g / 100mL; the concentration of the sodium aluminate compound solution, calculated as Al2O3, is 10g~25g / 100mL; the gelation temperature is 50℃~80℃; and the gelation pH value is 5.5~9.
0.
12. The method according to claim 9, characterized in that: Step 2) Add a sodium carbonate solution to control the pH of the material to 7.5~9.
5.
13. The method according to claim 9, characterized in that: In step 2), after adding a sodium carbonate solution, the pH of the system increases by 0.2 to 5.
0. The aging temperature is 30℃ to 95℃, and the aging time is controlled at 0.5h to 8h.
14. The method according to claim 13, characterized in that: In step 2), the pH of the system increases by 0.5 to 3.0 after adding a sodium carbonate solution; the aging temperature is 50℃ to 90℃; and the aging time is controlled at 1.5h to 4.5h.
15. The method according to claim 9, characterized in that: In step 3), the drying temperature is 60℃~200℃ and the drying time is 0.5h~12.0h, ensuring that the dry basis of the alumina dry adhesive powder is 60wt%~80wt%.
16. The method according to claim 15, characterized in that: In step 3), the drying temperature is 80℃~160℃ and the drying time is 1.0h~8.0h.
17. The method according to claim 9, characterized in that: In step 3), the aluminum hydroxide dry adhesive, after high-temperature calcination, exhibits the following properties: specific surface area of 200–500 μm. 2 / g, pore volume is 0.5~1.3mL / g, and average pore size is 5nm~16nm.
18. The method according to claim 6, characterized in that: The active metal in step (2) is introduced after the alumina dry adhesive is formed. The introduction is carried out by impregnation, either by equal volume impregnation or non-equal volume impregnation. Other additives are introduced before or simultaneously with the active metal. The additives are selected from one or more of silicon, phosphorus, fluorine and boron.
19. The method according to claim 6, characterized in that: The drying temperature in step (2) is 50℃~200℃, the drying time is 0.5h~20h, the calcination temperature is 350℃~900℃, and the calcination time is 0.5h~20h.
20. The method according to claim 19, characterized in that: The drying temperature in step (2) is 110℃~160℃ and the drying time is 1h~6h; the calcination temperature is 350℃~600℃ and the calcination time is 1h~6h.
21. A method for hydrogenation treatment, characterized in that: The method uses the hydrogenation catalyst described in any one of claims 1-5, and the operating conditions are as follows: VGO with a dry point of not less than 500°C is used as the feedstock, the total reaction pressure is 6.0 MPa ~ 20.0 MPa, and the volume hourly space velocity is 0.3 h⁻¹. -1 ~3.0 h -1 The hydrogen-to-oil ratio is 400:1 to 1800:1, and the reaction temperature is 300℃ to 420℃.
Citation Information
Patent Citations
Macropore alumina supporter and its preparation method
CN100371077C
Heavy oil hydrogenating treatment catalyst and preparation method thereof
CN101332430B
Preparation method of hydrodemetallization catalyst
CN106140187A
Hydrogenating catalyst and its preparing process
CN1302848A
Catalyst for heavy oil hydrotreatment and preparation method and application thereof
CN111097435A